Anti-tumour active gold(i), palladium(ii) and ruthenium(ii) complexes with thio- and selenoureato ligands: a comparative study. Issue 14 (21st March 2018) - Molter, Anja; Kathrein, Stefanie; Kircher, Brigitte; Mohr, Fabian
Abstract : A comparative study of biological activity (cytotoxicity, apoptosis induction, ROS production) of gold(i ), palladium(ii ) and ruthenium(ii ) complexes with chalcogenourea ligands. Abstract : We report the results of a comparative study of the biological activity of a series of gold(i ), palladium(ii ) and ruthenium(ii ) complexes containing deprotonated thio- and selenoureato ligands. A library of compounds was prepared and characterised by spectroscopic methods and the solid-state structures of several derivatives were determined by single crystal X-ray diffraction. The in vitro activity of these compounds was evaluated in mammary and ovarian carcinoma, acute lymphatic and acute and chronic myeloid leukemia cell lines. At lower concentrations Ru- and Pd-containing compounds displayed stronger anti-cancer effects than the gold compounds. In all cases, the selenium derivatives proved to be more active than the corresponding sulfur compounds.